Labour market flexibility and policy coordination in a monetary union - Anssi Rantala (Bank of Finland, 2003)
Sufficiently flexible labour markets are considered an important precondition for countries to benefit from membership in the monetary union.Economic policy coordination within the European Community is extensive and includes issues related to labour market structures.In this paper we study the determination of flexibility of the labour market and, ultimately, of wages in a member country of the monetary union.As a starting point, the analysis assumes that each country's government, in formulating its labour market policy, decides the degree of nominal wage flexibility in light of the fact that this involves political costs that increase with the degree of wage flexibility.The study then focuses on the effects of monetary union membership on each country's prospects for coordination of economic policies - specifically labour market policies.The study shows that coordination of labour market policies contributes to greater nominal wage flexibility in member countries.However, coordination of labour market policies will be effective only if unemployment is persistent or under discretionary monetary policy.From the perspective of macroeconomic stability, there is no particular need for coordinating labour market policies among member countries if the common central bank can credibly precommit to a low inflation target or if fluctuations in unemployment are white noise.
URN:NBN:fi:bof-20140807410
Keywords: E52; E58; E61; J51; 330; wage flexibility; economic policy coordination; credibility; precommitment